The Resurgence of Military Coups and Democratic Relapse in Africa (Adeoye Akinola (ed.)) - Martial , Fanga Agbor (Scientia Militaria - South African Journal of Military Studies, 2025)
The Resurgence of Military Coups and Democratic Relapse in Africa edited by Adeoye Akinola, Cham: Palgrave Macmillan, 2024, 258 pages, ISBN 978-3-031-51018-2.